TO INVESTIGATE THE EFFECT OF THE PASTEURISATION PROCESS ON TRACE ELEMENTS IN DONOR BREAST MILK. Issue 9 (17th August 2016) - Taufek, Nor Mohd; Cartwright, David; Hewavitharana, Amitha; Koorts, Pieter; McConachy, Helen; Shaw, Nick; Whitfield, Karen; Davies, Mark
Abstract : Aim: To investigate the effect of the pasteurisation process on trace elements in donor breast milk. Method: Premature infants often receive donor breast milk when the mother is unable to produce sufficient breast milk. It is widely accepted that donor milk has considerable advantages over formula milk.1 The Royal Brisbane and Women's Hospital (RBWH) has a milk bank that receives milk donated by women which undergoes a pasteurisation process.2 This study investigated the effect of pasteurisation on a range of trace elements in donor milk. A total of 14 participants who donated to the milk bank were recruited in this study. A 2 ml sample was collected pre- and post- pasteurisation, and frozen at −80 °C. Post-natal age of the milk was documented. Inductively-coupled plasma mass-spectrometry was used to analyse the following trace elements – zinc (Zn), copper (Cu), selenium (Se), manganese (Mn), iodine (I), iron (Fe), molybdenum (Mo) and bromine (Br). The study received ethical approval from RBWH and The University of Queensland Ethics Committee. Results: No significant difference was found between the levels of any of the trace elements tested pre- and post-pasteurisation. The following p-values were calculated – Zn (0.82), Cu (0.80), Se (0.97), Mn (0.63), I (0.99), Fe (0.05), Mo (0.41), Br (0.59). The following ranges in mcg/L of trace elements were calculated – Zn (365.4–5460.0), Cu (157.6–820.5), Se (10.6–23.7), Mn (0.55–3.24), I (66.4–215.3), Fe (101.5–473.1), Mo (0.20–5.45), Br (704.9–3379.0). Spearman's rank correlation analysis showed significant correlations between post-natal age of milk and trace elements – Zn (ρ=−0.578), Se (ρ=−0.627). Fe (ρ=−0.704), and Mo (ρ=−0.534). No significant correlation was found for Cu, Mn, I, and Br. Conclusion: This study found that the pasteurisation process had minimal effect on trace element levels in donor breast milk. However, it was noted that there was a correlation between post-natal age of donor milk and Zn, Se, Fe and Mo. Further work is needed to establish factors that may influence levels of trace elements in donor milk such as post-natal age.